The Role of Government Support and User Innovativeness to Entrepreneurs (Case study of SME’s in Depok, Indonesia) - Sasotya Pratama; Eka Sri Dana Afriza; Liza Agustina Maureen Nelloh (Sekolah Tinggi Manajemen IPMI, 2020)
This study aims to examine the influence of external and internal factors, in this case government support and owner-manager innovation, on the attitude of owner-managers of MSMEs towards FINTECH. This study uses the Structural Equation Modeling - Partial Least Square approach using SmartPLS version 3.2.4 to examine the research hypotheses. The respondents of this study were 64 MSME owner-managers in Depok, West Java. The study indicates that government support and owner-manager innovation have a significant and positive influence on their attitudes towards FINTECH. The imperative results of this study recommend FINTECH business owners to support government activities in inspiring and motivating MSME business owners in Depok to continue developing personal creativities that represent the innovations of each owner-manager of MSME.